"Believe in yourself and your skills": EPIC interview of Lynred's CTO, Pierre Jenouvrier. Issue 3 (15th June 2022) - Pozo, Jose
Abstract: Jose Pozo, EPIC's former director of technology, portraits Pierre Jenouvrier, CTO of Lynred, a manufacturer of detectors covering the entire infrared spectrum from short to very‐long wavelength IR.